Soil Solarization A non Chemical Method of Pest Control - Pramanik, Pragati; Maity, Aniruddha (Indian Farming, 2015)
The global changes and the constant increase in the erosion of the natural ecosystem emphasize the importance of soil solarization as a viable non chemical integrated pest management tool in agricultural production systems. As an established soil-borne pests control method, the effectiveness of soil solarization is well demonstrated under various agroecosystems, both in regions with high levels of solar radiation and in cloudy weather condition. Future research should aim at the development of improved technology, e.g. cheaper and more environmentally accepted mulching technology; large-scale application technologies; and new plastic formulations for improved soil temperature transmission in the vertical soil profile. These improvements should extend the use of this technology beyond the season limitations and make soil solarization suitable for marginal climatic regions and for less profitable crops. Also, these improvements will expand the range of the controlled pests and reduce the duration of the process.